Faktor-Faktor yang Mempengaruhi Investasi Swasta di Indonesia - Sutawijaya, Adrian; Zulfahmi, Z (Jurnal Trikonomika, 2013)
Exports and investment play an important role in the economy of a country that is open. Exports will generate foreign exchange, foreign exchange to finance imports of capital goods and raw materials required in the production process that will create added value for the economy. The variables examined in this study is the difference in private sector investment plans, loan interest rates, government spending, and Gross Domestic Bruto (GDP). Research on the analysis using the method of least squares OLS (Ordinary Least Square). Results of regression test based on the theory, statistical and econometric criteria. The results of this study are interest rates significantly have a positive affect on the private investment. GDP will have a positive effect on investment and also government spending has a positive effect on private investment.